Seasonal and Spatial Water Pollution Status at The Rivers Estuaries in Cirebon Region - Izhamil Hidayah; Hedi Indra Januar; Dwiyitno Dwiyitno; Nining Betawati Prihantini (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2021)
Cirebon has 18 rivers that flow into the Java Sea. The Cirebon rivers play an important role in several sectors such as industrial, agriculture, household, and also aquaculture. The increasing anthropogenic activities, may have affected the health and quality of the Cirebon rivers and the surrounding area. This study aimed to determine the water pollution level of Cirebon rivers based on the Storage and Retrieval (STORET) and Pollution Index approaches. The study was conducted at seven different rivers located in the districts (kabupaten) and municipals (kotamadya) of Cirebon. The observation was performed during the end of the west monsoon (March 2019) as well as the beginning (July 2019) and the end of the east monsoon (November 2019). The STORET score of the Cirebon district rivers were between -10 and -20, which is categorized as lightly to moderately polluted. Similarly, most of the Cirebon municipal rivers were moderately contaminated throughout the year (-18 to -30). In contrast, the Pollution Index (PI) values of all observed rivers were between 1.0 to 5.0 which are categorized as lightly polluted.